2017
DOI: 10.1590/1980-57642016dn11-020002
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus in the pathophysiology of Alzheimer's disease

Abstract: Both Alzheimer's disease (AD) and type 2 diabetes mellitus (DM) are two common forms of disease worldwide and many studies indicate that people with diabetes, especially DM, are at higher risk of developing AD. AD is characterized by progressive cognitive decline and accumulation of β-amyloid (Aβ) forming senile plaques. DM is a metabolic disorder characterized by hyperglycemia in the context of insulin resistance and relative lack of insulin. Both diseases also share common characteristics such as loss of cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 97 publications
(136 reference statements)
0
28
0
3
Order By: Relevance
“…Insulin resistance, which is a hallmark of type 2 diabetes, has a strong relationship to low‐grade, sterile inflammation, as shown, for example, by substantial upregulation of IL‐6, and activation of the NLRP3 inflammasome . Whether brain insulin resistance has consequences similar to those in type 2 diabetes, or whether it may represent a separate type of pathology referred to as type 3 diabetes, remains to be a matter of debate. Recently, effects of hyperinsulinemia were reported concerning the clearance of Aβ peptides over the blood‐brain barrier, however, with divergent results in Aβ 1‐40 and Aβ 1‐42 , details that will need further clarification with regard to their pathological consequences.…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Insulin resistance, which is a hallmark of type 2 diabetes, has a strong relationship to low‐grade, sterile inflammation, as shown, for example, by substantial upregulation of IL‐6, and activation of the NLRP3 inflammasome . Whether brain insulin resistance has consequences similar to those in type 2 diabetes, or whether it may represent a separate type of pathology referred to as type 3 diabetes, remains to be a matter of debate. Recently, effects of hyperinsulinemia were reported concerning the clearance of Aβ peptides over the blood‐brain barrier, however, with divergent results in Aβ 1‐40 and Aβ 1‐42 , details that will need further clarification with regard to their pathological consequences.…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…These conflicting results suggest that NSAIDs do not improve AD pathogenesis directly in the brain, but that systemic inflammation, such as that seen with rheumatoid arthritis, might affect the brain pathologically. Recent evidence also suggests that inflammatory diseases, such as osteoporosis, diabetes, cancer and infection, are possibly implicated in brain disorders, and that these diseases could affect brain function through immune responses elicited in the periphery; that is, through neuroimmune communication. Furthermore, treatment strategies against such diseases might influence brain function and the macroenvironment, as reported for cancer‐related cognitive impairment or HIV‐associated neurocognitive disorder, possibly leading to the onset of brain disorders.…”
Section: Neuroinflammation and The Interaction Between Brain And Perimentioning
confidence: 99%
“…Management of Type 2 Diabetes Mellitus (T2DM) is also an important AD prevention strategy (76). A meta-analysis reported that four out of five studies evaluating the association between T2DM and APOE ε4 carrier status on AD risk had positive associations and three were statistically significant, with odds ratios that ranged from 2.4-5.0 (77).…”
Section: Ad Comorbidity Considerationsmentioning
confidence: 99%